2019
DOI: 10.11591/ijpeds.v10.i2.pp720-730
|View full text |Cite
|
Sign up to set email alerts
|

Backstepping control of two-mass system using induction motor drive fed by voltage source inverter with ideal control performance of stator current

Abstract: <p>This paper describes the design and the simulation of a non-linear controller for two-mass system using induction motor basing on the backstepping method. The aim is to control the speed actual value of load motor matching with the speed reference load motor, moreover, electrical drive’s respone ensuring the “fast, accurate and small overshoot” and reducing the resonance oscillations for two-mass system using induction motor fed by voltage source inveter with ideally control performance of stator curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In practice there is always a deviation between the calculated and the actual values of the parameters. In addition, they also depend on the load torque, the moment of inertia, and coefficients of the mechanical structure connecting the motor such as damping coefficient d and shaft-stiffness c [12] and [13]. This affects the stability and control quality of the IM drive system.…”
Section: Design the Backstepping Control For The Speed Control Loopmentioning
confidence: 99%
See 3 more Smart Citations
“…In practice there is always a deviation between the calculated and the actual values of the parameters. In addition, they also depend on the load torque, the moment of inertia, and coefficients of the mechanical structure connecting the motor such as damping coefficient d and shaft-stiffness c [12] and [13]. This affects the stability and control quality of the IM drive system.…”
Section: Design the Backstepping Control For The Speed Control Loopmentioning
confidence: 99%
“…It has been shown that when operating in a wide range, the performance of the system degrades with the use of PI control [9][10][11]. Along with the strong development of hardware, nonlinear controllers [12,13] have been applied successfully in electrical drive systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The backstepping control system is a non-linear control method based on the theorem of Lyapunov. Due to its recursive design and systematic methodology, the backstepping control design methods got many attention [19][20][21][22][23]. Unlike the feedback linearization technique with issues such as the precise model requirement, the backstepping strategy provides a choice of design instruments to accommodate nonlinearities.…”
Section: Introductionmentioning
confidence: 99%